Performance of two ELISAs for antifilaggrin autoantibodies, using either affinity purified or deiminated recombinant human filaggrin, in the diagnosis of rheumatoid arthritis. Issue 9 (1st September 2001) - Nogueira, L; Sebbag, M; Vincent, C; Arnaud, M; Fournié, B; Cantagrel, A; Jolivet, M; Serre, G
Abstract : OBJECTIVE: To develop a standardisable enzyme linked immunosorbent assay (ELISA), using human filaggrin, for detection of antifilaggrin autoantibodies in rheumatoid arthritis (RA). To compare the diagnostic performance of the ELISA with those of reference tests: "antikeratin antibodies" ("AKA"), and antibodies to human epidermis filaggrin detected by immunoblotting (AhFA-IB). METHODS: Two ELISAs were developed using either affinity purified neutral-acidic human epidermis filaggrin (AhFA-ELISA-pur) or a recombinant human filaggrin deiminated in vitro (AhFA-ELISA-rec) as immunosorbent. Antifilaggrin autoantibodies were assayed in 714 serum samples from patients with well characterised rheumatic diseases, including 241 RA and 473 other rheumatic diseases, using the two ELISAs. "AKA" and AhFA-IB tests were carried out in the same series of patients. The diagnostic performance of the four tests was compared and their relationships analysed. RESULTS: The titres of "AKA", AhFA-IB, and the AhFA-ELISAs correlated strongly with each other. The diagnostic sensitivity of the AhFA-ELISA-rec, which was better than that of AhFA-ELISA-pur, was 0.52 for a specificity of 0.95. This performance was similar to those of "AKA" or AhFA-IB. However, combining AhFA-ELISA-rec with AhFA-IB led to a diagnostic sensitivity of 0.55 for a specificity of 0.99. CONCLUSION: A simple and easily standardisable ELISA for detection of antifilaggrin autoantibodies was developed and validated on a large series of patients using a citrullinated recombinant human filaggrin. The diagnostic performance of the test was similar to that of the "AKA" and AhFA-IB. Nevertheless, combining the AhFA-ELISA-rec with one of the other tests clearly enhanced the performance.